Study the Physicochemical Property of Basil Mucilage Powder and Applying for Development of Weight Control Beverage - Sangsuriyawong, Anantita; Phongsrikun, Supitchlada; Sinchaipanit, Pornrat; Peasura, Napassorn; Sirivarasai, Jintana (Burapha Science Journal, 2026)
The objective of this study was to analyze the physicochemical properties of basil mucilage for the development of weight control beverage. The extraction yield of the basil seed mucilage powder was about 15% by weight. Basil mucilage powder (100 g) contained 1.65 g protein, 0.82 g fat, 5.22 g ash, 86.5 g carbohydrates, and 5.8% moisture content. In addition, basil mucilage powder contained about 78% by weight of dietary fiber that was composed of about 21% soluble fiber and 57% insoluble fiber. Basil mucilage powder showed very high swelling property (40%), water holding value about 140 g/g, particle size range between 100-120 mesh, and 0.25 of water activity. The result of microbiological analysis showed that total plate count was 6.6 x 103 CFU/g, Escherichia coli was less than 3 MPN/g, and Salmonella was not detected in 25 g of sample. The development of an orange flavor and sugar free beverage powder was further studied by using the extracted basil mucilage powder. A beverage formulation with the highest sensory acceptance score (n = 6, 5-points hedonic scale) contained 6 g basil mucilage powder, 1.5 g sorbitol, 0.045 g sucralose, 0.6 g citric acid, 0.06 g salt, 0.15 g orange flavor, and 0.03 g of orange food coloring per 1 sachet or 1 serving size. A basil mucilage beverage product will be further studied the influence satiation in human studies.